2010
DOI: 10.1002/zaac.201000173
|View full text |Cite
|
Sign up to set email alerts
|

Homodinuclear f–f and Heterodinuclear f–p Lanthanide Helicates

Abstract: Lanthanide helicates are of interest due to their ability to emit either in the visible or in the NIR region. In this context it is important to prepare heterodinuclear helicates and to use them for the investigation of intramolecular communication processes between different complex units. In here we describe the ligand synthesis and selfassembly of homo-and heterodinuclear helicates based on β-diketonate, catechol-acyl hydrazone and 2-amido-8-hydroxyquinoline li-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The other compounds are expected to exhibit this property as well, and efforts to obtain larger single crystals to determine the scintillation capabilities are underway. Potentially, these materials may also be applicable to catalysis and luminescence. …”
Section: Resultsmentioning
confidence: 99%
“…The other compounds are expected to exhibit this property as well, and efforts to obtain larger single crystals to determine the scintillation capabilities are underway. Potentially, these materials may also be applicable to catalysis and luminescence. …”
Section: Resultsmentioning
confidence: 99%
“…41 Whilst much emphasis has been placed on the development of transition metal based supramolecular systems 37,[42][43][44][45][46] Ln III -directed selfassembly formation has only recently experienced considerable attention, offering a route towards large molecular fabrications such as bundles, helicates or hierarchical systems such as clusters or metal organic frameworks (MOFs). [47][48][49][50][51][52][53][54][55] Since the Ln III possess larger coordination numbers than the transition metal ions, ligand binding sites and metal coordination geometries play an even more important role in determining and controlling the overall structure of the resulting system.…”
Section: The Coordination Chemistry Of the Lanthanidesmentioning
confidence: 99%
“…In particular helicates [4][5][6][7][8][9][10] have been extensively examined. Pioneering work by Hannon et al showed that a triply-stranded [Fe 2 L 3 ] 4+ (L = N,N 0 -(methanediyldibenzene-4,1-diyl)bis[1-(pyridin-2-yl)methanimine]) helicate [11] had extremely interesting biological properties [12,13].…”
Section: Introductionmentioning
confidence: 99%